2021
DOI: 10.36351/pjo.v37i2.1123
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Diabetic Retinopathy and Factors for Suboptimal Diabetic Control in Type 2 Diabetic Patients in a Trust Hospital of Pakistan

Abstract: Purpose:  To find out the frequency of diabetic retinopathy and factors responsible for poor diabetic control in patients with type 2 diabetes in a trust hospital. Place and duration of Study:  Akhtar Saeed Medical College, from January 2018 to December 2019. Study Design:  Descriptive cross-sectional study. Methods:  Total 395 diabetic patients belonging to lower socioeconomic class were included in the study. Type 1diabetes, age below 20 years, high myopia, papilledema, dense cataract, corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…15 One recent study conducted in Pakistan showed much less frequency of diabetic retinopathy compared to this study. 16 This may be explained due to different sample sizes and patient selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…15 One recent study conducted in Pakistan showed much less frequency of diabetic retinopathy compared to this study. 16 This may be explained due to different sample sizes and patient selection criteria.…”
Section: Discussionmentioning
confidence: 99%